Peel-based carbon dots as well as preparation method and application thereof
The nitrogen- and magnesium co-doped carbon dot probes prepared by hydrothermal reaction solve the problems of poor optical stability and high cytotoxicity of optical probes, and realize the application of high photostability and low cytotoxicity in tumor detection.
Patent Information
- Application Number
- CN202511139848.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-08-14
- Publication Date
- 2025-12-16
AI Technical Summary
Existing optical probes have poor optical stability and high cytotoxicity, making it difficult to meet the needs of real-time navigation during surgery.
Using grapefruit or orange peel powder as carbon, magnesium, and nitrogen sources, nitrogen and magnesium co-doped carbon dots are prepared under high temperature and pressure through hydrothermal reaction, forming Mg-N-CDs fluorescent probes with surfaces rich in hydroxyl, carboxyl, and amino groups, thus achieving green synthesis and surface functionalization.
The prepared Mg-N-CDs fluorescent probe emits bright blue-green light at 510 nm, exhibits good photostability, and maintains a fluorescence intensity of over 95% after continuous excitation for 30 min. It also has low cytotoxicity and is suitable for tumor detection.
Smart Images

Figure CN121134745A_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of nanobiomedical imaging technology, and in particular to a carbon dot based on fruit peel, its preparation method, and its application. Background Technology
[0002] Cancer has a high incidence and mortality rate, and early diagnosis and treatment are effective methods for cancer prevention. Traditional tumor detection mainly relies on two pathways: imaging examinations and pathological sampling. Imaging examinations mainly include X-ray computed tomography (CT), magnetic resonance imaging (MRI), ultrasound imaging, and positron emission tomography (PET). Among them, CT reconstructs tomographic images through multi-angle X-ray attenuation information and can detect solid lesions with a diameter of several millimeters, but the soft tissue contrast is limited and it is accompanied by ionizing radiation; MRI provides high-resolution soft tissue contrast by utilizing hydrogen proton relaxation differences, but the scan time is long, the cost is high, and it is not sensitive to calcifications; ultrasound imaging is based on high-frequency sound wave reflection differences and can observe blood flow and lesion morphology in real time, but it is easily affected by the operator's experience and the patient's body size, and the resolution decreases rapidly with depth; PET uses radiolabeled glucose analogs such as 18F-FDG to show metabolically active areas, has high sensitivity, but comes with a significant radiation dose and the equipment is expensive. Pathological sampling relies on surgical or puncture biopsy to obtain tissue, which is then embedded in paraffin, sectioned, stained with hematoxylin and eosin, and interpreted by a pathologist under an optical microscope. It is considered the "gold standard" for diagnosis. However, its invasiveness brings risks of bleeding, infection, and tumor dissemination, and it cannot fully sample micrometastases.
[0003] Compared to traditional methods, optical probes offer relatively high detection sensitivity. However, most existing optical probes are based on heavy metal quantum dots or organic fluorescent dyes. The former contains toxic elements such as Cd and Pb, which can cause the release of heavy metal ions and chronic toxicity if left in the body for a long time; the latter has poor photostability, with fluorescence intensity decreasing by more than 60% after 30 minutes of continuous excitation, making it difficult to meet the real-time navigation requirements during surgery. Summary of the Invention
[0004] The main objective of this invention is to propose a carbon dot based on fruit peel, its preparation method, and its application, aiming to solve the problems of poor optical stability and high cytotoxicity of existing optical probes.
[0005] To achieve the above objectives, the present invention provides a method for preparing carbon dots based on fruit peel, comprising the following steps:
[0006] Step S10: Mix the carbon source and deionized water to obtain a reaction solution;
[0007] Step S20: After the reaction solution undergoes hydrothermal reaction, it is filtered, dialyzed, and freeze-dried to obtain carbon dots based on the fruit peel.
[0008] In step S10, the carbon source includes at least one of grapefruit peel powder and orange peel powder, and in step S20, the hydrothermal reaction temperature is 160-260°C and the reaction time is 6-30 hours.
[0009] In one embodiment, the hydrothermal reaction is carried out at a temperature of 180–240°C for 12–24 hours.
[0010] In one embodiment, the hydrothermal reaction is carried out at a temperature of 200–240°C for 18–24 hours.
[0011] In one embodiment, the solid content of the reaction solution is 7% to 8%.
[0012] In one embodiment, step S20 specifically involves placing the reaction solution in a hydrothermal reactor for hydrothermal reaction, cooling it to obtain a brownish-yellow suspension, filtering the brownish-yellow suspension through a microporous membrane, then dialyzing it in deionized water using a dialysis bag, and finally freeze-drying it to obtain the fruit peel-based carbon dots.
[0013] In one embodiment, the microporous filter membrane has a pore size of 0.22 μm, the dialysis bag has a molecular weight cutoff of 1000 Da, and the dialysis duration is 40–50 h.
[0014] In one embodiment, step S10 specifically involves dispersing the carbon source in deionized water, stirring and mixing to obtain a reaction solution.
[0015] In one embodiment, the obtained carbon dots based on the pericarp have a particle size of 2.59 nm, an emission wavelength of 500–510 nm, and maintain a fluorescence intensity of over 95% after continuous excitation for 30 min. They are also free from cytotoxicity and hematologic toxicity within the physiological concentration range.
[0016] The present invention also provides a method for preparing carbon dots based on fruit peel as described above, resulting in carbon dots based on fruit peel.
[0017] The present invention also provides an application of the above-described fruit peel-based carbon dots in tumor detection.
[0018] 1. The technical solution of this invention uses grapefruit peel powder or orange peel powder as the carbon source, magnesium source, and nitrogen source. By controlling the temperature and time of the hydrothermal reaction, under the high temperature and high pressure of the hydrothermal reaction, the carbon-containing organic matter in the grapefruit peel powder or orange peel powder gradually decomposes to form carbon dots. At the same time, the nitrogen element in the grapefruit peel powder or orange peel powder decomposes at high temperature to produce nitrogen-containing active species that react with the active hydroxyl and carboxyl groups on the surface of the carbon dots and bond to the surface of the carbon dots. In addition, some nitrogen atoms replace some carbon atoms in the conjugated framework of the carbon dots, realizing nitrogen doping. The Mg in the grapefruit peel powder or orange peel powder... 2+Magnesium doping is achieved by coordinating with active hydroxyl groups, carboxyl groups, and amino groups formed by nitrogen doping on the surface of carbon dots. This allows for simultaneous nitrogen and magnesium co-doping during the hydrothermal carbonization process, enabling green synthesis and surface functionalization of carbon dots in a one-step hydrothermal method. After the reaction, impurities are removed by filtration and dialysis, and high-purity Mg-N-CDs fluorescent probes based on fruit peel are obtained by freeze-drying.
[0019] 2. The Mg-N-CDs prepared by this invention are rich in hydrophilic functional groups such as hydroxyl, carboxyl, and amino groups on their surface, which endows them with excellent water solubility and biocompatibility. With an ultra-small particle size of 2.59 nm, they emit bright blue-green light at 510 nm, and the fluorescence intensity remains above 95% after continuous excitation for 30 min, showing good photostability. In the MTT assay, the cell viability rate of Mg-N-CDs at a concentration of 200 μg / mL is >90%, exhibiting extremely low cytotoxicity. Attached Figure Description
[0020] To more clearly illustrate the technical solutions in the embodiments of the present invention or the prior art, the drawings used in the description of the embodiments or the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For those skilled in the art, other drawings can be obtained based on the structures shown in these drawings without creative effort.
[0021] Figure 1 This is a flowchart illustrating one embodiment of the method for preparing carbon dots based on fruit peel, and a schematic diagram showing their entry into cells.
[0022] Figure 2 This is a transmission electron microscope (TEM) image of Mg-N-CDs prepared in Example 1 of the present invention; Figure 2 The scale bar for Figure A is 50nm, for Figure B it is 20nm, for Figure C it is 10nm, and for Figure D it is 2nm.
[0023] Figure 3 This is a particle size distribution diagram of Mg-N-CDs prepared in Example 1 of the present invention;
[0024] Figure 4 The image shows the X-ray photoelectron spectroscopy (XPS) spectrum of Mg-N-CDs prepared in Example 1 of this invention.
[0025] Figure 5 Figure A shows the Fourier Transmission Infrared (FT-IR) spectrum of Mg-N-CDs prepared in Example 1 of this invention; Figure B shows the Fourier Transmission Infrared (FT-IR) spectrum of Mg-N-CDs prepared in Example 11 of this invention.
[0026] Figure 6Figure A shows the UV-Vis absorption spectrum of Mg-N-CDs prepared in Example 11 of this invention; Figure B shows the fluorescence emission spectrum (PL) of Mg-N-CDs prepared in Example 11 of this invention as a function of excitation wavelength; Figure C shows the UV-Vis absorption spectrum of Mg-N-CDs prepared in Example 1 of this invention; Figure D shows the fluorescence emission spectrum (PL) of Mg-N-CDs prepared in Example 1 of this invention as a function of excitation wavelength.
[0027] Figure 7 Figure A shows the cytotoxicity of Mg-N-CDs prepared in Example 11 of this invention; Figure B shows the cytotoxicity of Mg-N-CDs prepared in Example 1 of this invention.
[0028] Figure 8 The images shown are optical micrographs of Mg-N-CDs prepared in Example 1 of this invention before and after entering HeLa cells.
[0029] Figure 9 Confocal microscopy cell imaging of Mg-N-CDs prepared in Example 1 of this invention before and after entering HeLa cells;
[0030] Figure 10 The fluorescence emission (PL) spectra of Mg-N-CDs prepared in Examples 1-10 of this invention are shown.
[0031] Figure 11 The X-ray photoelectron spectrum of Mg-N-CDs prepared in Example 11 of this invention;
[0032] Figure 12 The fluorescence emission (PL) spectra of Mg-N-CDs prepared in Examples 11-20 of this invention are shown.
[0033] The realization of the objective, functional features and advantages of the present invention will be further explained in conjunction with the embodiments and with reference to the accompanying drawings. Detailed Implementation
[0034] The technical solutions of the embodiments of the present invention will be clearly and completely described below with reference to the accompanying drawings. Obviously, the described embodiments are only a part of the embodiments of the present invention, and not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those of ordinary skill in the art without creative effort are within the scope of protection of the present invention.
[0035] Furthermore, the use of "and / or" or "and / or" throughout the text implies three parallel solutions. For example, "A and / or B" includes solution A, solution B, or a solution that simultaneously satisfies both A and B. Additionally, the technical solutions of the various embodiments can be combined with each other, but this must be based on the ability of those skilled in the art to implement them. If the combination of technical solutions is contradictory or impossible to implement, it should be considered that such a combination of technical solutions does not exist and is not within the scope of protection claimed by this invention.
[0036] Cancer has a high incidence and mortality rate, making early diagnosis and treatment effective methods for prevention. Traditional tumor detection mainly relies on two pathways: imaging examinations and pathological sampling. Imaging examinations primarily include X-ray computed tomography (CT), magnetic resonance imaging (MRI), ultrasound imaging, and positron emission tomography (PET), but these methods suffer from problems such as ionizing radiation, insensitivity to calcifications, rapid resolution degradation with depth, and high costs. Pathological sampling is invasive, posing risks of bleeding, infection, and tumor dissemination, and cannot comprehensively sample micrometastases. Compared to traditional methods, optical probes offer relatively higher detection sensitivity. However, existing optical probes mostly use heavy metal quantum dots or organic fluorescent dyes as building blocks. The former contains toxic elements such as Cd and Pb, which can cause heavy metal ion release and chronic toxicity if retained in the body for a long time; the latter has poor photostability, with fluorescence intensity decaying by more than 60% after 30 minutes of continuous excitation, making it difficult to meet the real-time navigation requirements during surgery.
[0037] like Figure 1 As shown, this invention provides a method for preparing carbon dots based on fruit peel, comprising the following steps:
[0038] Step S10: Mix the carbon source and deionized water to obtain a reaction solution;
[0039] Step S20: After the reaction solution undergoes hydrothermal reaction, it is filtered, dialyzed, and freeze-dried to obtain carbon dots based on the fruit peel.
[0040] In step S10, the carbon source includes at least one of grapefruit peel powder and orange peel powder. In step S20, the hydrothermal reaction temperature is 160–260°C, and the reaction time is 6–30 h. Specifically, the magnesium content in orange peel is approximately 0.1–0.3 mg / g (dry weight), and the total nitrogen content is approximately 10–25 mg / g (dry weight); the magnesium content in grapefruit peel is approximately 0.2–0.4 mg / g (dry weight), and the total nitrogen content is approximately 8–20 mg / g (dry weight).
[0041] The technical solution of this invention uses grapefruit peel powder or orange peel powder as carbon, magnesium, and nitrogen sources. By controlling the temperature and time of the hydrothermal reaction, a one-step hydrothermal method is used to prepare fruit peel-based carbon dots Mg-N-CDs with excellent fluorescence performance and good biocompatibility. Specifically: First, grapefruit peel powder or orange peel powder is mixed evenly with deionized water to obtain a reaction solution. Then, the reaction solution is subjected to a hydrothermal reaction, controlling the reaction temperature at 160-240℃ and the reaction time at 6-30h. Grapefruit peel powder or orange peel powder is rich in various carbon-containing organic compounds such as cellulose, hemicellulose, and lignin. Using it as a carbon source, under the high temperature and pressure of a hydrothermal reaction, carbon-containing organic matter first undergoes dehydration and decarboxylation reactions, causing the macromolecular chain to decompose into smaller molecular fragments. These smaller fragments then form a conjugated carbon skeleton through condensation and cyclization reactions. As the reaction continues, the size of the carbon skeleton gradually decreases, forming carbon dots. Simultaneously, nitrogen in the grapefruit peel decomposes at high temperature to produce nitrogen-containing reactive species such as NH3. NH3 reacts with active hydroxyl and carboxyl groups on the surface of the carbon dots and bonds to them. Additionally, some nitrogen atoms replace some carbon atoms in the conjugated carbon skeleton of the carbon dots, achieving nitrogen doping. Mg in the grapefruit peel... 2+ Magnesium doping is achieved by coordinating with active hydroxyl groups, carboxyl groups, and amino groups formed by nitrogen doping on the surface of carbon dots. This means that nitrogen and magnesium co-doping is simultaneously achieved during the hydrothermal carbonization process to form carbon dots. After the reaction, large particulate impurities are first removed by filtration, followed by dialysis to further remove smaller molecular weight impurities. Finally, freeze-drying is performed to remove moisture while maintaining the microscopic bonding and activity of the nitrogen-magnesium co-doped carbon dots, yielding high-purity pericarp-based carbon dot Mg-N-CDs. The resulting Mg-N-CDs have a surface rich in hydrophilic functional groups such as hydroxyl, carboxyl, and amino groups, endowing them with excellent water solubility and biocompatibility. Nitrogen doping can improve the defects and structural stability of the carbon dot surface, thereby enhancing its fluorescence performance and fluorescence stability. Simultaneously, the presence of nitrogen can better stabilize magnesium in the carbon dots, further improving the structural stability of the carbon dots and achieving surface passivation, thus increasing quantum yield. Magnesium doping can also improve the fluorescence emission wavelength of the carbon dots, enhance biocompatibility, and reduce cytotoxicity. Through nitrogen-magnesium synergy, Mg-N-CDs based on fruit peels with excellent fluorescence performance, good biocompatibility, high quantum yield, and low cytotoxicity are obtained. The resulting Mg-N-CDs aqueous dispersion can be stably stored for more than six months at 4℃ in the dark without significant precipitation or fluorescence quenching, further demonstrating its stability.
[0042] Furthermore, the preparation method of this application uses edible fruit waste grapefruit peel or orange peel as a carbon source precursor. The raw materials are widely available and inexpensive, realizing high-value utilization of waste and having obvious advantages in large-scale production and green sustainable development. The hydrothermal method completes carbonization and nitrogen-magnesium co-doping in one step without the need for subsequent modification or surface passivation treatment. The entire process does not require inert gas protection and the synthesis process is simple.
[0043] In embodiments of the present invention, the hydrothermal reaction temperature is 180–240°C and the reaction time is 12–24 h.
[0044] The technical solution of this invention further optimizes the temperature and time of the hydrothermal reaction, enabling the carbon source to fully carbonize and form a sufficient number of carbon dots, while ensuring sufficient reaction and doping of nitrogen and magnesium elements. If the reaction temperature is too high or the reaction time is too long, the carbon source will excessively decompose or agglomerate, thus affecting the structure and number of carbon dots, and consequently the microstructure and properties of the resulting Mg-N-CDs. If the reaction temperature is too low or the reaction time is too short, the carbonization reaction of the carbon source will be insufficient, thus affecting the formation of carbon dots, and consequently affecting the doping of nitrogen and magnesium.
[0045] In an embodiment of the present invention, the hydrothermal reaction temperature is 200–240°C and the reaction time is 18–24 h.
[0046] The technical solution of the present invention promotes the full progress of the hydrothermal reaction by controlling the reaction temperature of the hydrothermal reaction to 200-240℃ and the reaction time to 18-24h, thereby obtaining high-performance Mg-N-CDs.
[0047] In an embodiment of the present invention, in step S10, the solid content of the reaction solution is 7% to 8%, that is, 7 to 8 g of carbon source is dispersed in every 100 mL of water.
[0048] The technical solution of this invention ensures the full conduction of hydrothermal carbonization and nitrogen / magnesium doping reactions by rationally setting the solid content of the reaction solution. When the solid content of the reaction solution is low, the concentration of raw materials is low, and the probability of molecular collisions is low, thus affecting the reaction rate of carbonization and doping. When the solid content of the reaction solution is high, the viscosity of the reaction system is high, the uniformity of raw material dispersion is poor, and the raw materials are prone to agglomeration, resulting in uneven nitrogen / magnesium doping, which in turn affects the structure and properties of the product.
[0049] In an embodiment of the present invention, step S20 specifically involves placing the reaction solution in a hydrothermal reactor for hydrothermal reaction, cooling it to obtain a brownish-yellow suspension, filtering the brownish-yellow suspension through a microporous membrane, then dialyzing it in deionized water using a dialysis bag, and freeze-drying it to obtain carbon dots based on the fruit peel.
[0050] The technical solution of this invention involves placing the reaction solution in a hydrothermal reactor to provide the necessary high-temperature and high-pressure environment for the hydrothermal reaction. After the reaction is completed, a yellow suspension is obtained due to the presence of unreacted impurities. The product is then purified by first filtering to remove large particulate impurities, then dialysis to further remove impurities with smaller molecular weights, and finally freeze-drying to remove moisture, resulting in high-purity Mg-N-CDs.
[0051] In an embodiment of the present invention, the pore size of the microporous filter membrane is 0.22 μm, the molecular weight cutoff of the dialysis bag is 1000 Da, and the dialysis duration is 40–50 h.
[0052] The technical solution of this invention, by reasonably setting the pore size of the microporous filter membrane, ensures the thorough removal of large particulate impurities while avoiding the drawback of slow filtration rate caused by excessively small pore size. Simultaneously, it reasonably sets the molecular weight cutoff of the dialysis bag; the molecular weight of carbon dots is generally greater than 1000 Da, while the molecular weight of small molecule impurities is less than 1000 Da. During dialysis, small molecule impurities can pass through the dialysis bag into deionized water for removal. By reasonably setting the dialysis time, it ensures the thorough removal of small molecule impurities and improves product purity.
[0053] In an embodiment of the present invention, step S10 specifically involves dispersing the carbon source in deionized water and stirring to obtain a reaction solution. Specifically, the carbon source is placed in a hydrothermal reactor lined with polytetrafluoroethylene, deionized water is added, and the mixture is stirred thoroughly to obtain a reaction solution. The carbon source needs to be pretreated. The pretreatment specifically involves removing the white pith from fresh grapefruit or orange peel, cutting it into small pieces, washing it with deionized water, drying it at 70-90°C to constant weight, pulverizing it, and passing it through a 100-mesh sieve to obtain dried grapefruit peel powder.
[0054] The technical solution of this invention involves pre-treating fresh grapefruit or orange peels to remove impurities, resulting in grapefruit or orange peel powder with uniform and small particle size, which provides favorable conditions for the full carbonization reaction. The carbon source is first dispersed in deionized water to facilitate thorough and uniform mixing of the materials, providing favorable conditions for the uniform doping of magnesium and nitrogen.
[0055] In the embodiments of the present invention, the obtained carbon dots based on the fruit peel have a particle size of 2.59 nm, an emission wavelength of 500-510 nm, and a fluorescence intensity of more than 95% after continuous excitation for 30 min. They are not cytotoxic or hematologic within the physiological concentration range.
[0056] The technical solution of this invention controls the particle size of carbon dots based on fruit peel to the nanoscale, resulting in a larger specific surface area, making it easier to achieve nitrogen and magnesium doping. The uniform size also improves fluorescence color development and facilitates penetration of cell membranes or biological tissues, enabling binding to specific cells. The emission wavelength is 500–510 nm, producing visible blue-green light for easy color observation. After continuous excitation for 30 minutes, the fluorescence intensity remains above 95%, indicating high photostability, long lifespan, and high detection accuracy. Within the physiological concentration range, it exhibits no cytotoxicity or hematologic toxicity, avoiding damage to receptors during use.
[0057] The present invention also provides a method for preparing carbon dots based on fruit peel, as described above, to obtain carbon dots based on fruit peel.
[0058] The technical solution of the present invention uses the above-mentioned specific preparation method to obtain carbon dots based on fruit peel. The carbon dots based on fruit peel have the characteristics of excellent fluorescence performance, good biocompatibility, high quantum yield and low cytotoxicity.
[0059] The present invention also provides an application of the above-mentioned peel-based carbon dots in tumor detection.
[0060] The technical solution of this invention applies high-performance Mg-N-CDs with specific microstructures to tumor detection. By utilizing the multiple non-covalent interactions between the carboxyl, hydroxyl, and amino groups enriched on the surface of Mg-N-CDs and the highly expressed receptors on the tumor cell membrane, specific recognition and enrichment of cancer cells can be achieved without the need for additional conjugated antibodies or targeting ligands. This enables high-contrast tumor imaging, breaking through the multiple bottlenecks of traditional imaging and existing probes in terms of sensitivity, specificity, safety, cost, and environmental friendliness. It provides a green, efficient, and low-toxicity new strategy for early tumor diagnosis, intraoperative real-time navigation, and photothermal / photodynamic combined therapy, and has broad clinical application prospects.
[0061] The technical solution of the present invention will be further described in detail below with reference to specific embodiments and accompanying drawings. It should be understood that the following embodiments are merely illustrative of the present invention and are not intended to limit the present invention. Unless otherwise specified, the experimental methods used in the following embodiments are conventional methods. Unless otherwise specified, the reagents and materials used in the following embodiments are commercially available.
[0062] Example 1
[0063] A method for preparing carbon dots based on fruit peel includes the following steps:
[0064] Step S10: Remove the white pith from fresh grapefruit peel, cut it into small pieces, wash with deionized water, dry at 80℃ to constant weight, pulverize and pass through a 100-mesh sieve to obtain dried grapefruit peel powder. Weigh 3.0g of the above grapefruit peel powder and place it in a polytetrafluoroethylene-lined hydrothermal reactor, add 40mL of deionized water, and stir thoroughly for 30min to obtain a reaction solution.
[0065] Step S20: Seal the reaction vessel and react at a constant temperature of 240℃ for 24h. After natural cooling to room temperature, a brownish-yellow suspension is obtained. The obtained brownish-yellow suspension is filtered through a 0.22μm microporous membrane and then dialyzed in deionized water for 48h using a dialysis bag with a molecular weight cutoff of 1000Da. After freeze-drying, Mg-N-CDs are obtained with a yield of 28% (based on carbon element conversion rate).
[0066] Depend on Figure 2The TEM image shown (tested using a JEOL JEM-2100F field emission transmission electron microscope) reveals a large number of nearly spherical nanoparticles with clear boundaries that are uniformly dispersed without obvious agglomeration. The overall morphology proves that the preparation method of this application can obtain ultra-small Mg-N-CDs with uniform size and good dispersion, providing a structural basis for their excellent fluorescence properties and cell penetration ability. Figure 2 The D-image under medium to high magnification shows that the lattice fringe spacing of Mg-N-CDs is about 0.21 nm, corresponding to the (100) crystal plane of graphite carbon, indicating that there are short-range ordered graphite micro-regions inside the material; no obvious amorphous coating layer is seen on the outer layer, indicating that its surface is mainly composed of functional groups rather than a thick oxide layer.
[0067] Randomly measured 200 Mg-N-CDs particles, and obtained the particle size as follows: Figure 3 The distribution diagram shown shows that the average particle size of Mg-N-CDs prepared in Example 1 is about 2.59 nm, and the particle size distribution is narrow (standard deviation <0.3 nm), which further indicates that the Mg-N-CDs particles prepared in Example 1 have good uniformity.
[0068] To further confirm the presence of magnesium and nitrogen in Mg-N-CDs, the prepared Mg-N-CDs were subjected to XPS analysis (using Thermo Fisher Scientific K-Alpha Plus X-ray photoelectron spectroscopy). The results are as follows: Figure 4 As shown. By Figure 4 As shown in the E-plot, Mg-N-CDs exhibit distinct characteristic peaks for C 1s, N 1s, O 1s, and Mg 1s near 285 eV, 400 eV, 532 eV, and 1305 eV, respectively, indicating that Mg-N-CDs contain C, O, N, and Mg elements. Figure 4 As shown in Figure A, the C 1s peak result is 284.6 eV (indicating that it is caused by sp...). 2 Three sets of peaks were observed: 286.2 eV (indicating CO / CN bonds) and 288.4 eV (indicating C=O bonds); [The text abruptly ends here, likely due to an incomplete sentence or missing information.] Figure 4 As shown in Figure B, N 1s exhibits pyrrole-type nitrogen at 399.8 eV, indicating that nitrogen is doped into the carbon framework; from Figure 4 As shown in Figure C, Mg 1s is located at 1305 eV, corresponding to a Mg-O coordination structure; from Figure 4 As shown in the D-plot, the O 1s peak results are 532 eV (indicating the presence of CO bonds) and 533 eV (indicating good water absorption).
[0069] Depend on Figure 5 As shown in Figure A (using a Nicolet IS 5 Fourier transform infrared spectrometer), the FT-IR plot at 3233 cm⁻¹ shows that... -1A broad and strong absorption peak is observed at 2923 cm⁻¹, attributed to the OH / NH stretching vibrations of hydroxyl and amino groups, indicating the presence of abundant hydrophilic groups on the Mg-N-CDs surface; -1 The sharp peak corresponds to alkyl CH stretching, indicating the presence of a small amount of aliphatic segments in the carbon skeleton; 1580 cm⁻¹ -1 The obvious absorption band nearby corresponds to the stretching of the carboxyl C=O group, 1046 cm⁻¹ -1 The shoulder peak at that location originates from the CO bending and CN stretching of the carboxyl or carbonyl groups; 1100cm -1 The signals on the left and right sides further indicate COC. These characteristic peaks collectively confirm that the surface of Mg-N-CDs is rich in polar functional groups such as hydroxyl, carboxyl, and amino groups, which endow it with excellent water solubility and further bioconjugation ability. The FT-IR spectrum shows that Mg-N-CDs contain H element.
[0070] Depend on Figure 6 As shown in Figure C (measured using a LAMBDA 950 UV-Vis absorption spectrometer), within the 200-400 nm range, the absorption spectrum exhibits three absorption bands at approximately 220 nm, 275 nm, and 345 nm. The strong absorption near 220 nm corresponds to sp... 2 The π→π* transition in the hybrid carbon network indicates that CDs have a conjugated carbon framework; the moderate intensity absorption at 275 nm is caused by the n→π* transition induced by oxygen-containing functional groups on the surface, indicating that there are a large number of active oxygen-containing functional groups on the Mg-N-CDs surface; the shoulder peak at 345 nm is caused by the defect state introduced by nitrogen / magnesium doping, which provides a radiative recombination channel for the carbon dot surface energy trap.
[0071] Depend on Figure 6 As shown in Figure D (measured using a Hitach F-4600 fluorescence spectrometer), when the excitation wavelength is fixed at 440 nm, the fluorescence emission spectrum exhibits a sharp and symmetrical single peak at 510 nm, displaying bright blue-green luminescence. The obtained carbon dots, under 440 nm excitation, show an emission quantum yield of ≥42% at 510 nm, and fluorescence decay of <5% after 30 minutes of continuous laser irradiation, demonstrating both high brightness and excellent photostability. Further observation of the excitation-emission contour plot reveals that as the excitation wavelength gradually redshifts from 400 nm to 460 nm, the emission peak position continuously redshifts from 500 nm to 530 nm, while the peak intensity first increases and then decreases, exhibiting a typical excitation wavelength dependence. This dependence stems from the broad defect energy level distribution on the Mg-N-CDs surface; different excitation energies preferentially excite defect states at different depths, thus causing the emission peak position to shift with the excitation wavelength. Figure 6 The C and D plots in the figure confirm that the Mg-N-CDs have a wide absorption window, significant defect luminescence characteristics, and good excitation tunability, providing spectroscopic evidence for their application in cell imaging and multicolor labeling.
[0072] To investigate the cytotoxicity of Mg-N-CDs, an MTT assay was performed. Specifically, the MTT assay was used to detect the cytotoxicity of Mg-N-CDs. HeLa cells were grown at a density of 8 × 10⁸ cells per well. 3 Cells were seeded into 96-well plates at a volume of 100 μL per well. The plates were incubated in a cell culture incubator (5% CO2, 37℃) for 24 h. Then, 100 μL of different concentrations of Mg-N-CDs were added, and the plates were incubated for another 24 h. After washing three times with PBS, 100 μL of fresh medium containing MTT was added to each well, and the plates were incubated for another 4 h. The supernatant was discarded, and 100 μL of DMSO was added to each well. The plates were gently shaken, and the absorbance at 490 nm was measured using a Molecular Devices SpectraMax i3x microplate reader. The results were recorded and processed. Using the absorbance of untreated cells as 100%, the cell viability at different concentrations of N-CDs was calculated. The results are shown below. Figure 7 As shown in Figure B. (From...) Figure 7 As shown in Figure B, when the concentrations of Mg-N-CDs were 50 μg / mL, 100 μg / mL, 150 μg / mL, and 200 μg / mL, the relative survival rates were close to or slightly higher than 90%. Furthermore, the relative survival rate of HeLa cells did not decrease significantly with increasing Mg-N-CDs concentration, and there was no statistically significant difference compared to the blank control (0 μg / mL). This indicates that Mg-N-CDs are virtually non-toxic to cells within the tested concentration range and possess excellent biocompatibility, providing a safe dosage basis for its subsequent in vitro and in vivo imaging applications.
[0073] Cell imaging studies were conducted using A549 cells as a cell model. Figure 8 The optical microscope images shown (tested using an inverted fluorescence microscope) reveal that A549 cells adhered to the cell wall, exhibiting intact morphology and clear edges. Almost no fluorescence signal was observed in the bright-field images (Images A-D), but in the fluorescence channels after the addition of Mg-N-CDs (Images E-F), all cell outlines were uniformly delineated by blue-green light (emission at 510 nm), demonstrating that the Mg-N-CDs probe successfully entered the cells and maintained good fluorescence performance. Furthermore, no obvious cell shrinkage or floating was observed, suggesting low toxicity. Meanwhile, from... Figure 9The confocal laser scanning microscopy images shown (tested using a Leica TCS SP8 fluorescence confocal microscope) were captured at 405 nm excitation and 510 nm collection channels, respectively. The 3D reconstructed images reveal that Mg-N-CDs are not only distributed across the cell membrane but also abundantly accumulated in the cytoplasm, forming a bright green fluorescent cloud. The fluorescence in the nucleus region is weak, indicating that the Mg-N-CDs probes did not significantly penetrate the nuclear membrane. Z-stack scanning shows clear signals at all levels from the basement to the apex, without aggregation or quenching, further confirming that Mg-N-CDs possess excellent photostability, biocompatibility, and intracellular diffusion capacity, making them suitable for in vivo tumor imaging.
[0074] To investigate the application of Mg-N-CDs prepared in Example 1 in tumor detection, they were intravenously injected into tumor-bearing mice containing tumor cells at a dose of 5 mg / kg. Firstly, the abundant amino and carboxyl groups on the surface of Mg-N-CDs can electrostatically interact with negatively or positively charged groups such as folate receptors and integrins highly expressed on the tumor cell membrane. Secondly, the ultra-small particle size of 2.59 nm endows it with enhanced penetration and retention effects (EPR effect), enabling it to pass through the tumor vascular space and remain in the tumor tissue for a long time. Under the above dual targeting effect, the fluorescence signal at the tumor site in the tumor-bearing mice reached its peak at 2 hours, with a signal-to-noise ratio (tumor / normal tissue fluorescence ratio) as high as 6.8. Furthermore, almost no fluorescence residue was observed in the major organs (heart, liver, spleen, lung, and kidney) after 24 hours, indicating that the Mg-N-CDs probe has excellent tumor specificity and in vivo clearance.
[0075] Example 2
[0076] A method for preparing carbon dots based on fruit peel, which differs from Example 1 only in that the hydrothermal reaction time in step S20 is 6 hours. The other steps are roughly the same as in Example 1 and will not be described again here.
[0077] Example 3
[0078] A method for preparing carbon dots based on fruit peel, which differs from Example 1 only in that the hydrothermal reaction time in step S20 is 12 hours. The other steps are roughly the same as in Example 1 and will not be described again here.
[0079] Example 4
[0080] A method for preparing carbon dots based on fruit peel, which differs from Example 1 only in that the hydrothermal reaction time in step S20 is 18 hours. The other steps are roughly the same as in Example 1 and will not be described again here.
[0081] Example 5
[0082] A method for preparing carbon dots based on fruit peel, which differs from Example 1 only in that the hydrothermal reaction time in step S20 is 30 hours. The other steps are roughly the same as in Example 1 and will not be described again here.
[0083] Example 6
[0084] A method for preparing carbon dots based on fruit peel, which differs from Example 1 only in that the hydrothermal reaction temperature in step S20 is 160°C. The other steps are roughly the same as in Example 1 and will not be described again here.
[0085] Example 7
[0086] A method for preparing carbon dots based on fruit peel, which differs from Example 1 only in that the hydrothermal reaction temperature in step S20 is 180°C. The other steps are roughly the same as in Example 1 and will not be described again here.
[0087] Example 8
[0088] A method for preparing carbon dots based on fruit peel, which differs from Example 1 only in that the hydrothermal reaction temperature in step S20 is 200°C. The other steps are roughly the same as in Example 1 and will not be described again here.
[0089] Example 9
[0090] A method for preparing carbon dots based on fruit peel, which differs from Example 1 only in that the hydrothermal reaction temperature in step S20 is 220°C. The other steps are roughly the same as in Example 1 and will not be described again here.
[0091] Example 10
[0092] A method for preparing carbon dots based on fruit peel, which differs from Example 1 only in that the hydrothermal reaction temperature in step S20 is 260°C. The other steps are roughly the same as in Example 1 and will not be described again here.
[0093] The fluorescence intensity (excitation wavelength of 440 nm) of the Mg-N-CDs prepared in Examples 1-10 was detected, and the results are as follows: Figure 10 As shown. By Figure 10 As shown in Figure A, when the excitation wavelength is 440 nm, the emission peak appears at 510 nm, exhibiting bright blue-green fluorescence. Figure 10 Figure A shows that as the hydrothermal reaction time gradually increases, the fluorescence intensity of Mg-N-CDs generally exhibits a trend of first increasing and then decreasing. When the hydrothermal reaction time is 24 hours, the fluorescence intensity increases significantly. Meanwhile, Figure 10Figure B shows that as the hydrothermal reaction temperature gradually increases, the fluorescence intensity of Mg-N-CDs generally exhibits a trend of first increasing and then decreasing. When the hydrothermal reaction temperature reaches 240℃, the fluorescence intensity increases significantly. This indicates that the Mg-N-CDs prepared by the hydrothermal reaction at a reaction time of 24h and a temperature of 240℃ have a superior microstructure, resulting in the strongest fluorescence intensity. Too short or too long a reaction time, or too low or too high a temperature, will weaken the optical performance due to insufficient or excessive carbonization. The Mg-N-CDs prepared in Examples 1-10 showed a fluorescence decay of <5% after 30 minutes of continuous laser irradiation, indicating good photostability.
[0094] Example 11
[0095] A method for preparing carbon dots based on fruit peel, which differs from Example 1 only in that the carbon source in step S10 is orange peel, while the other steps are largely the same as in Example 1 and will not be repeated here.
[0096] Depend on Figure 11 As shown in the XPS graph, Figure 11 spectral profile and Figure 4 Almost identical: It was also observed that Mg-N-CDs showed obvious characteristic peaks of C1s, N 1s, O 1s, and Mg 1s near 285eV, 400eV, 532eV, and 1305eV, respectively, indicating that the Mg-N-CDs prepared using orange peel powder as a carbon source contained four elements: C, O, N, and Mg.
[0097] Depend on Figure 5 As shown in Figure B, the FT-IR plot shows that Figure 5 The infrared spectra of Figure B are basically similar to those of Figure A. Figure 6 As shown in Figures A and B, the UV-Vis absorption spectrum and the fluorescence emission spectrum varying with excitation wavelength are consistent with those in Example 1. Figure 6 The diagrams in Figures C and D are basically similar.
[0098] Depend on Figure 7 The cytotoxicity test results in Figure A show that the Mg-N-CDs prepared in Example 11 are almost non-toxic to cells and have excellent biocompatibility within the tested concentration range.
[0099] It is evident that when grapefruit peel powder is replaced with lycium barbarum peel powder, the performance of the resulting Mg-N-CDs remains good.
[0100] Example 12
[0101] A method for preparing carbon dots based on fruit peel, which differs from Example 11 only in that the hydrothermal reaction time in step S20 is 6 hours. The other steps are roughly the same as in Example 11 and will not be described again here.
[0102] Example 13
[0103] A method for preparing carbon dots based on fruit peel, which differs from Example 11 only in that the hydrothermal reaction time in step S20 is 12 hours. The other steps are roughly the same as in Example 11 and will not be described again here.
[0104] Example 14
[0105] A method for preparing carbon dots based on fruit peel, which differs from Example 11 only in that the hydrothermal reaction time in step S20 is 18 hours. The other steps are roughly the same as in Example 11 and will not be described again here.
[0106] Example 15
[0107] A method for preparing carbon dots based on fruit peel, which differs from Example 11 only in that the hydrothermal reaction time in step S20 is 30 hours. The other steps are roughly the same as in Example 11 and will not be described again here.
[0108] Example 16
[0109] A method for preparing carbon dots based on fruit peel, which differs from Example 11 only in that the hydrothermal reaction temperature in step S20 is 160°C. The other steps are roughly the same as in Example 11 and will not be described again here.
[0110] Example 17
[0111] A method for preparing carbon dots based on fruit peel, which differs from Example 11 only in that the hydrothermal reaction temperature in step S20 is 180°C. The other steps are roughly the same as in Example 11 and will not be described again here.
[0112] Example 18
[0113] A method for preparing carbon dots based on fruit peel, which differs from Example 11 only in that the hydrothermal reaction temperature in step S20 is 200°C, and the other steps are roughly the same as in Example 11, and will not be described again here.
[0114] Example 19
[0115] A method for preparing carbon dots based on fruit peel, which differs from Example 11 only in that the hydrothermal reaction temperature in step S20 is 220°C. The other steps are roughly the same as in Example 11 and will not be described again here.
[0116] Example 20
[0117] A method for preparing carbon dots based on fruit peel, which differs from Example 11 only in that the hydrothermal reaction temperature in step S20 is 260°C. The other steps are roughly the same as in Example 11 and will not be described again here.
[0118] The fluorescence intensity and ultraviolet absorbance of the Mg-N-CDs prepared in Examples 11-20 were measured, and the results are as follows: Figure 12 As shown. Figure 12 spectral profile and Figure 10 Almost identical: both observed an emission peak at 510 nm under 440 nm excitation and absorption characteristics at 220 nm, 275 nm, and 345 nm, and the excitation dependence trend also remained synchronous. Figure 10 and Figure 12 This demonstrates that regardless of whether grapefruit peel powder or orange peel powder is used as the carbon source, Mg-N-CDs with highly reproducible optical properties can be obtained under the same hydrothermal conditions. Furthermore, it shows that when grapefruit peel powder is replaced with citrus peel powder, the performance of the resulting Mg-N-CDs remains good. The Mg-N-CDs prepared in Examples 11-20 exhibited a fluorescence decay of <5% after 30 minutes of continuous laser irradiation, indicating good photostability.
[0119] The above description is merely an exemplary embodiment of the present invention and does not limit the patent scope of the present invention. Any equivalent structural transformations made using the contents of the present invention specification and drawings under the technical concept of the present invention, or direct / indirect applications in other related technical fields, are included within the patent protection scope of the present invention.
Claims
1. A method for preparing carbon dots based on fruit peel, characterized in that, Includes the following steps: Step S10: Mix the carbon source and deionized water to obtain a reaction solution; Step S20: After the reaction solution undergoes hydrothermal reaction, it is filtered, dialyzed, and freeze-dried to obtain carbon dots based on the fruit peel; In step S10, the carbon source includes at least one of grapefruit peel powder and orange peel powder, and in step S20, the hydrothermal reaction temperature is 160-260°C and the reaction time is 6-30 hours.
2. The method for preparing carbon dots based on fruit peel as described in claim 1, characterized in that, The hydrothermal reaction is carried out at a temperature of 180–240°C for 12–24 hours.
3. The method for preparing carbon dots based on fruit peel as described in claim 2, characterized in that, The hydrothermal reaction is carried out at a temperature of 200–240°C for 18–24 hours.
4. The method for preparing carbon dots based on fruit peel as described in claim 1, characterized in that, In step S10, the solid content of the reaction solution is 7% to 8%.
5. The method for preparing carbon dots based on fruit peel as described in claim 1, characterized in that, Step S20 specifically involves placing the reaction solution in a hydrothermal reactor for hydrothermal reaction, cooling it to obtain a brownish-yellow suspension, filtering the brownish-yellow suspension through a microporous membrane, then dialyzing it in deionized water using a dialysis bag, and finally freeze-drying it to obtain the fruit peel-based carbon dots.
6. The method for preparing carbon dots based on fruit peel as described in claim 5, characterized in that, The microporous filter membrane has a pore size of 0.22 μm, the dialysis bag has a molecular weight cutoff of 1000 Da, and the dialysis duration is 40–50 h.
7. The method for preparing carbon dots based on fruit peel as described in claim 5, characterized in that, Step S10 specifically involves dispersing the carbon source in deionized water, stirring and mixing to obtain a reaction solution.
8. The method for preparing carbon dots based on fruit peel as described in claim 1, characterized in that, The obtained carbon dots based on the pericarp have a particle size of 2.59 nm and an emission wavelength of 500–510 nm. After continuous excitation for 30 min, the fluorescence intensity remains above 95%, and there is no cytotoxicity or hematologic toxicity within the physiological concentration range.
9. Carbon dots based on fruit peel prepared by the method for preparing carbon dots based on fruit peel as described in any one of claims 1 to 8.
10. The application of the carbon dots based on fruit peel prepared by the method of any one of claims 1 to 8, or the carbon dots based on fruit peel as described in claim 9, in tumor detection.